Transformational Leaders in the Canadian Counselling and Psychotherapy Association: An Interview with Blythe Shepard - Kozak, Lindsay Morgan; Gray, Neal D. (Canadian Journal of Counselling and Psychotherapy, 2018)
This article provides highlights from an interview with Dr. Blythe Shepard, a prominent leader in the counselling profession in Canada. The article focuses on Dr. Shepard’s involvement with various professional counselling organizations in Canada and advocacy projects developed to increase awareness of the profession. Dr. Shepard also outlines her hopes for the future of the profession in Canada, and perceived obstacles which need to be addressed.